Application of Fuzzy Delphi on the factor influencing buying behaviour for organic food / Nur Syafiqah Abdul Rashid and Mohd Halimi Ab Hamid - Abdul Rashid, Nur Syafiqah; Ab Hamid, Mohd Halimi (College of Computing, Informatics and Media, UiTM Perlis, 2023)
There are challenges for organic food retailers to create a marketing strategy to develop their business because they cannot identify the main factors and patterns in consumer buying behaviour towards organic food. This study aims to determine the main factor influencing consumer buying behaviour for organic food and rank the factors based on the priority in purchase intention. To achieve such objective, the Fuzzy Delphi has been used to determine ranking of sub-factors for five factors which are price, behavioural intention, subjective norm, attitude and consumer knowledge. The primary data was collected by distributing questionnaires to five experts which includes retailers with organic food business backgrounds and consumers of organic food in Kuantan, Pahang. The findings derived shown that the most influential sub-factor affecting consumer purchasing behaviour towards organic food under behavioural intention was that people usually consider purchasing organic food that meets their taste with fuzzy score 0.68 while for subjective norms, the first ranking was concept of organically grown food with fuzzy score 0.68. Furthermore, the first ranking for price factor was reasonable price with fuzzy score 0.68 and for consumer knowledge, the first ranking was people are familiar with products that comes in environmentally safe packages with fuzzy score 0.68. Lastly, the first ranking under attitude factor was organic food keeps the consumer fit and healthy with fuzzy score 0.76. Based on this outcome, it shows that Fuzzy Delphi is a method that can help experts to make decisions under complicated situations and rank all the sub-factors with precision.